Growth Performance of The Huntsman Spider (Spariolenus Aratta) Based on Different Feed Sources - Mwale, Tehillah; Olweny, Calleb; Andika, Darius (International Journal of agricultural Extension, 2022)
Spiders, though not heavily researched, hold the possible key to new and innovative development, by not only being a source of biological control for farmers aiding in the reduction in the use of pesticides and insecticides on farms. But also, by playing a role in food security. However, in spite of this potential, arachnids (spiders) have not been traditionally included into the formal scientific education as a feed source despite their abundance, familiarity and ease of maintenance in captivity. The objective of this study was to evaluate the effect of selected feed sources on the performance of huntsman spider (Spariolenus aratta). The spiders were reared for a period of 14 weeks, with a total of 90 spiders under observation, fed on three feed sources; crickets, black soldier fly and fruit flies. The experimental design was completely randomized block design, replicated 3 times, with 10 spiders per experimental unit. The results were analyzed through the use of R software with least significant test and Pearson correlation test performed in order to determine the significant difference between the types of feed. Analysis for association was undertaken to determine if there was a relationship between the leg span and abdominal length and width during the period of the study (6 weeks). Results showed that spiders fed on crickets had significantly (P≤0.05) higher growth rate in comparison with those that were fed on black soldier fly larva and fruit flies. Additionally, there was positive association (r = 1) between feed in relation to; leg span growth, abdominal length as well as abdominal width during the period of the study. In conclusion based on the three feeds supplied to the spiders’, crickets were best in achieving leg and abdominal growth with means; 0.46cm for leg span, 0.34cm for abdominal length and 0.16cm for abdominal width.
Keywords: Black Soldier Fly Larva (BSF Larva); Crickets; Feed; Fruit Flies; Spiders